(3GdCQHYjf GdeNJGQI ef Sff CHj OGhOs - (3GHf YHO GdgGOi GdMfHdis; (3SdjeGf Hf GdCTYK Hf GSMGb Hf HTjQ GdGROj GdSLSJGfj, CHh OGhO,J (B275 (3g` s ((3hjhSa Hf eMeO GdUjOGhi (B((3JdejP GdeDda(B) s)
(3ChdgG (B:s
(3GdMOjK GdChd s
(3BNQgG (B:s
(3GdMOjK GdCQHYjf s
(3Vef eLehY , JQJjHgG (B: (3GdChds
(3Hg SeGYs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs